Tumor infiltrating lymphocytes in gastrointestinal tumors: Controversies and future clinical implications. (February 2017) - Solinas, Cinzia; Pusole, Grazia; Demurtas, Laura; Puzzoni, Marco; Mascia, Roberta; Morgan, Gilberto; Giampieri, Riccardo; Scartozzi, Mario
Highlights: Different techniques can be used for the assessment of tumor-infiltrating lymphocytes (TILs), providing information about the extent, composition, density and functional profile of the immune infiltrate with prognostic and predictive implications. High mutational load in microsatellite instable tumors is correlated with higher immune infiltration and better responses to the immune-checkpoint blockade. TILs might have future role in the selection of the ideal candidates for immunotherapy. Abstract: Chronic inflammation following infections, autoimmune diseases or exposure to environmental irritants plays a crucial role in tumor development and influences the host immune response to neoplastic cells. The presence of an anti-tumor immune infiltrate is often associated with better outcomes in gastro-intestinal primary cancers, particularly in those with high microsatellite instability (MSI-H). Immunotherapeutic drugs inhibiting the PD-1 and PD-L1 pathway showed promising results in the treatment of these patients in the metastatic setting. The aim of this review is to resume the role tumor infiltrating lymphocytes (TILs) play in gastrointestinal tumors, underlining their potential value as a prognostic and predictive biomarker. TILs assessment could identify subsets of patients with high extent of TILs and better prognosis, that could be spared from adjuvant systemic treatments. Immune infiltration parameters might be additional predictors of a greater benefit from the immunotherapy with the immune checkpoint blockade.